ANALISIS EKONOMI PEDAGANG MAKANAN TRADISIONAL DI PONTIAN JOHOR MALAYSIA - Muh. Zulkifli Murfat; Syamsuri Rahim; Imaduddin, Imaduddin; Amirullah, Amirullah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this community engagement is to provide guidance to the residents of Pontian, Johor, aiming to enhance their understanding of the economic value of Micro, Small, and Medium Enterprises (MSMEs), particularly in the context of the traditional food "gogos." Despite their familiarity with utilizing the internet as a tool to introduce their products, this initiative also elucidates the concept of the 4P marketing strategy (Product, Price, Place, Promotion). Special emphasis is placed on the realization that skillfully and accurately implementing the appropriate marketing strategy will empower the community to assess their performance by comparing it against predefined marketing targets. To achieve this, concrete steps in strategic marketing are meticulously crafted for each designed stage. This endeavor encompasses illustrative examples of marketing strategies for diverse businesses, encompassing SWOT analysis, such as market understanding, formulation of marketing objectives, configuration of the marketing mix, augmentation of brand awareness, and targeting mobile device users